Double-sided Uv viscosity-reducing film and preparation method thereof

By using toughened reinforced substrates and improved glue composition, the existing double-sided UV mucosa has been solved in terms of mechanical properties and chemical resistance, and has achieved higher toughness, impact resistance and chemical resistance, which is suitable for applications in modern electronics, automotive and optical industries.

CN119529690AInactive Publication Date: 2025-02-28NANTONG LIMENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889752.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing double-sided UV mucosa has shortcomings in mechanical properties, chemical resistance and adaptability to special application scenarios, and it is difficult to meet the rapid development needs of modern electronics, automobiles, optics and other industries.

Method used

The reinforced substrate is made of polyvinyl chloride, propylene oxide and polyethylene terephthalate, and nitrile rubber and nano calcium carbonate are added for toughening. Polyacrylic resin and modified photoinitiator are used to improve viscosity and cure effect, and antistatic agents and terephthalic acid are added to enhance toughness and chemical resistance.

Benefits of technology

The toughness, impact resistance and chemical resistance of the mucosal membrane are improved, allowing it to maintain stability and reliability in a variety of complex environments and conditions, ensuring a firm and long-lasting adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of double-sided Uv visbreaking films, in particular to a double-sided Uv visbreaking film and a preparation method thereof.The double-sided Uv visbreaking film is characterized in that a reinforcing base material is composed of polyvinyl chloride, epoxypropane and polyethylene glycol terephthalate, and nitrile rubber and nano calcium carbonate are added for toughening. Polyvinyl chloride has good chemical corrosion resistance and compatibility, polyethylene glycol terephthalate is high in strength and good in optical performance, nitrile rubber effectively improves toughness and endows oil resistance and chemical resistance, and nano calcium carbonate further enhances the toughness, so that the base material can bear large tensile force, pressure and external force impact and is not prone to breakage or damage, and the service life of the base material is prolonged. The stability and reliability of the viscosity-reducing film under various complex environments and using conditions are guaranteed, all the components have a synergistic effect, polymerization of acrylate monomers can be effectively initiated, glue is rapidly and evenly converted into a solid state from a liquid state, and it is guaranteed that the viscosity-reducing film is good in curing effect and firm and durable in adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of double-sided UV anti-viscosity film preparation, and in particular to a double-sided UV anti-viscosity film and a preparation method thereof. Background Art

[0002] In the field of modern industrial production and technological application, especially in the electronics, automobile, optics and other industries, there are increasingly stringent requirements for the temporary fixation and precise processing of materials. Double-sided UV anti-adhesive film came into being and has been widely used.

[0003] In the electronics industry, the manufacturing and assembly processes of many precision electronic components require the use of double-sided anti-sticking films to achieve temporary fixation and positioning of components. In the semiconductor chip packaging process, the chip needs to maintain a precise position between different process steps. Although the traditional double-sided anti-sticking film can provide a certain adhesive effect, as electronic components develop towards smaller sizes and higher integration, the comprehensive performance of the anti-sticking film has been challenged. On the one hand, the mechanical properties of the traditional anti-sticking film may not meet the requirements of bearing complex processing stresses at a tiny size, and it is easy to break or displace, affecting the yield of chip packaging; relying on double-sided anti-sticking film to fix optical components. However, due to the extremely high requirements of optical components for surface accuracy and optical performance, the traditional anti-sticking film may cause scratches, residual glue and other defects on the surface of the optical component due to its own strength, insufficient toughness or incomplete curing during the pasting and peeling process, thereby affecting the key performance indicators of the optical component such as transmittance and refractive index.

[0004] In summary, the existing double-sided UV anti-viscosity film has many deficiencies in mechanical properties, chemical resistance and adaptability to special application scenarios, and it is difficult to meet the needs of the rapid development of modern electronics, automobiles, optics and other industries. Therefore, it is urgent to develop a double-sided UV anti-viscosity film with better comprehensive performance. The present invention is based on such a background. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical solution adopted by the present invention to solve the technical problems is: a double-sided UV viscosity-reducing film, comprising the following weight components: 100-120 parts of a reinforcing substrate; 70-90 parts of a polyacrylic resin; 70-90 parts of an organic solvent; 2-8 parts of a curing agent; 0.1-4 parts of an antistatic agent; 0.2-5 parts of a modified photoinitiator; 0.5-5 parts of terephthalic acid; Polyacrylic acid resin is a high molecular polymer with good viscosity. During the UV curing process, polyacrylic acid resin will undergo a cross-linking reaction, so that the viscosity-reducing film has a certain hardness to maintain its shape after curing, and has sufficient elasticity to withstand a certain external force, thereby improving the performance of the viscosity-reducing film. Organic solvents are a type of liquid that can dissolve some organic compounds that are insoluble in water. In the preparation of double-sided UV viscosity-reducing film, it is mainly used to dissolve components such as resins so that the components can be evenly mixed to form a glue with good fluidity. Curing agent, also known as hardener, is a chemical substance that can react chemically with components such as resins in the glue to convert the glue from liquid to solid. In the double-sided UV viscosity-reducing film, antistatic agents can avoid electrostatic adsorption of impurities such as dust, or prevent electrostatic discharge from causing damage to electronic components, etc. The addition of terephthalic acid can improve the toughness of the viscosity-reducing film. It can react with components such as polyacrylic acid resin to form more complex chemical bonds in the polymer network structure of the viscosity-reducing film. When the viscosity-reducing film is stretched or bent by external force, these chemical bonds can absorb and disperse energy, preventing the viscosity-reducing film from brittle fracture.

[0006] Wherein, the specific preparation method of the reinforced substrate is as follows: Step S1: drying polyvinyl chloride, propylene oxide and polyethylene terephthalate respectively, and after drying, placing them in a reaction kettle for stirring, and obtaining a primary mixture after stirring; Step S2: adding a rubber toughening agent and a nanomaterial to the premix, and stirring again to obtain a premix; Step S3: adding the premix into a twin-screw extruder for mixing and plasticizing, extruding the prefabricated substrate in the shape of a sheet through a die after mixing, and cooling the premix to 40° C. by air cooling to obtain a reinforced substrate.

[0007] The present invention is further configured that the drying treatment of polyvinyl chloride, propylene oxide and polyethylene terephthalate in step S1 is drying in an oven at 80-100°C for 2-4 hours, the mass ratio of polyvinyl chloride, propylene oxide and polyethylene terephthalate is 30:30:40, the stirring speed is 500-1000 rpm, and the stirring time is 10-20 minutes. Polyvinyl chloride material, it also has good chemical corrosion resistance, can resist the erosion of some common organic solvents and acid and alkali solutions, and polyvinyl chloride has good compatibility with many glues and coatings. In the double-sided UV anti-viscosity film, this compatibility helps the glue to better adhere to the substrate and form a firm adhesive layer. It also has good impact resistance, polyethylene terephthalate has high strength, can withstand large tension and pressure, and can provide sufficient strength to prevent the glass sheet from falling off. It also has good optical properties, such as high transparency and suitable refractive index.

[0008] The present invention is further configured as follows: in the step S2, the rubber toughening agent is a nitrile rubber with an acrylonitrile content of 30%-40%, the nano material is nano calcium carbonate, the amount of the nitrile rubber is 5%-15% of the total mass of polyvinyl chloride, propylene oxide and polyethylene terephthalate, and the amount of the nano calcium carbonate is 1%-5% of the total mass of polyvinyl chloride, propylene oxide and polyethylene terephthalate. Nitrile rubber is an elastomer polymerized from butadiene and acrylonitrile. Adding nitrile rubber to the substrate can effectively improve toughness, and the nitrile group on the nitrile rubber molecular chain gives it oil resistance, chemical resistance and other characteristics; nano calcium carbonate has a small particle size, and when added to the substrate, it can be used as an effective toughening agent. Due to its small particle size and large specific surface area, it can produce a large amount of physical adsorption and chemical bonding with the polymer molecules of the substrate, and can play the role of a stress concentration point. Under the action of external force, it can induce silver streaks in the substrate and prevent the silver streaks from expanding into cracks, thereby improving the toughness of the substrate.

[0009] The present invention is further configured that the modified photoinitiator is specifically prepared as follows: Step A1: dissolving 4-methylbenzophenone in benzene, adding 48% hydrobromic acid solution, and heating to 60° C. under light to obtain an initial reactant; Step A2: adding 27.5% hydrogen peroxide to the initial reactant, keeping the temperature after the addition, then cooling to 20-30°C and adding bromine, washing the organic phase with a sodium carbonate solution to a weak alkaline state after the mixing is completed to obtain an organic phase; Step A3: adding triethanolamine to the organic phase, heating and refluxing to precipitate the quaternary ammonium salt in the solvent benzene in the form of a solid, and cooling to 60° C. to obtain a pre-reactant; Step A4: n-butyl isocyanate is added dropwise to the pre-reactant to carry out temperature-controlled reaction. After the reaction is completed, the temperature is lowered to 26° C., the product is separated by filtration, and the modified photoinitiator is obtained after drying.

[0010] The present invention is further configured as follows: the mass fraction of the 4-methylbenzophenone is 10%-30%, the mass fraction of benzene is 40%-60%, the mass fraction of hydrobromic acid solution is 5%-15%, the mass fraction of hydrogen peroxide is 3%-8%, the mass fraction of bromine is 2%-6%, the mass fraction of triethanolamine is 3%-10%, and the mass fraction of n-butyl isocyanate is 5%-12%. 4-methylbenzophenone initiates the polymerization of acrylate monomers in the viscosity-reducing glue solution, so that the glue is converted from liquid to solid, and the curing of the viscosity-reducing film is realized. Benzene mainly plays the role of a solvent in this system. It can dissolve 4-methylbenzophenone so that the reaction can be carried out in a homogeneous system. Because benzene has good solubility, it can ensure that 4-methylbenzophenone is evenly dispersed, so that the light-triggered reaction occurs evenly in the whole system, and the acidic environment of hydrobromic acid helps to regulate the rate and direction of the reaction, promotes the progress of certain reaction steps, such as under acidic conditions, it may be conducive to the stable existence of some intermediates, and hydrogen peroxide mainly plays an oxidizing role in the reaction. It can oxidize some intermediates to more active substances or participate in the oxidative modification of 4-methylbenzophenone; Bromine is a strong brominating agent. During the reaction, it can directly react with 4-methylbenzophenone to undergo bromination reaction, introducing bromine atoms into the molecular structure. The introduction of bromine atoms can change the electron cloud distribution and chemical activity of 4-methylbenzophenone, such as increasing its absorption range or absorption efficiency of UV light. Triethanolamine can participate in the synthesis of intermediates in the reaction. For example, it can react with products containing bromine atoms to form intermediates with a quaternary ammonium salt structure. This intermediate may have better solubility or compatibility with other components. n-Butyl isocyanate can react with the intermediate generated by the previous reaction to further modify the photoinitiator. Improve its compatibility with other components in the glue system, or adjust its ability and efficiency to produce active species under UV light irradiation, thereby optimizing the performance of the photoinitiator in the UV viscosity-reducing film curing process.

[0011] The present invention is further configured such that the illumination in step A1 is LED green light irradiation, the insulation time in step A2 is 30 minutes, and the heating and reflux time in step A3 is 1-8 hours.

[0012] The present invention is further configured to include the following steps: Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator and terephthalic acid are added into the reaction kettle in order, and each component is stirred and mixed after being added, and after the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer, and drying the coating to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compound a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0013] Acetone is a colorless, transparent liquid with strong solubility, which can quickly dissolve a variety of organic resins. Ethylenediamine is a colorless liquid with a strong ammonia smell. It has high reactivity with epoxy resin and can quickly solidify the glue. Dodecyltrimethylammonium chloride is a commonly used quaternary ammonium salt antistatic agent, which forms a conductive layer on the surface of the material to conduct static electricity away in time.

[0014] The present invention is further configured such that in step B1, the organic solution is acetone, the curing agent is ethylenediamine, and the antistatic agent is dodecyltrimethylammonium chloride.

[0015] The present invention is further configured such that the stirring speed in step B1 is 200-500 rpm, the stirring time is 5-10 min, and the drying temperature in step B2 is 80-130° C.

[0016] The beneficial effects of the present invention are as follows: 1. The present invention strengthens the substrate composed of polyvinyl chloride, propylene oxide and polyethylene terephthalate, and adds nitrile rubber and nano calcium carbonate for toughening. Polyvinyl chloride has good chemical corrosion resistance and compatibility, polyethylene terephthalate has high strength and good optical properties, nitrile rubber effectively improves toughness and imparts oil and chemical resistance, and nano calcium carbonate further enhances toughness, so that the substrate can withstand large tension, pressure and external force impact, is not easy to break or damage, and ensures the stability and reliability of the viscosity-reducing film in a variety of complex environments and use conditions.

[0017] 2. The present invention provides good viscosity by setting polyacrylic acid resin, and a cross-linking reaction occurs during the UV curing process, so that the viscosity-reducing film has both hardness and elasticity after curing, and can maintain its shape and withstand external forces. The modified photoinitiator is synthesized through a specific complex preparation process, and the components work synergistically to effectively initiate the polymerization of acrylate monomers, so that the glue quickly and evenly changes from liquid to solid, ensuring that the viscosity-reducing film has a good curing effect and is firmly and persistently adhered.

[0018] 3. The present invention can avoid electrostatic adsorption of dust impurities or prevent electrostatic discharge from damaging electronic components by setting an antistatic agent, and terephthalic acid improves the toughness of the anti-viscosity film and enhances its chemical resistance, so that it can resist corrosion from common organic solvents and acid and alkali solutions. When used in the fields of electronics and chemical industry, it can effectively protect the adhered components or materials, extend the service life of the anti-viscosity film and improve product quality. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses. Embodiment 1

[0020] Polyvinyl chloride, propylene oxide, polyethylene terephthalate, nitrile rubber and nano calcium carbonate were prepared.

[0021] Strengthening substrate preparation: Experimental Group 1 Step S1: placing polyvinyl chloride, propylene oxide and polyethylene terephthalate in a ratio of 30:30:40 in an oven at 80° C. and drying for 2 hours, placing the mixture in a reaction kettle and stirring the mixture at a speed of 500 rpm for 10 minutes to obtain a primary mixture; Step S2: adding 5% of a rubber toughening agent and 1% of a nanomaterial to the premix, and stirring again to obtain a premix; Step S3: adding the premix into a twin-screw extruder for mixing and plasticizing, extruding the prefabricated substrate in the shape of a sheet through a die after mixing, and cooling the premix to 40° C. by air cooling to obtain a reinforced substrate.

[0022] Experimental Group 2 Step S1: placing polyvinyl chloride, propylene oxide and polyethylene terephthalate in a ratio of 30:30:40 in an oven at 100° C. and drying them for 4 hours, placing them in a reaction kettle and stirring them at a speed of 1000 rpm for 20 minutes, and obtaining a primary mixture after the stirring is completed; Step S2: adding 15% of a rubber toughening agent and 5% of a nanomaterial to the premix, and stirring again to obtain a premix; Step S3: adding the premix into a twin-screw extruder for mixing and plasticizing, extruding the prefabricated substrate in the shape of a sheet through a die after mixing, and cooling the premix to 40° C. by air cooling to obtain a reinforced substrate.

[0023] Preparation method of double-sided UV anti-viscosity film Experimental group b1 Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator and terephthalic acid are added into the reaction kettle in the order of 70:70:2:0.1:0.2:0.5. After each component is added, it is stirred and mixed at 200 rpm for 5 minutes. After the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer in the experimental group 1, and drying the coating at 80° C. to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compound a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0024] Experimental group b2 Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator and terephthalic acid are added into the reaction kettle in the order of 90:90:8:4:5:5. After each component is added, it is stirred and mixed at 500 rpm for 10 minutes. After the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer in the experimental group 2, and drying the coating at 130° C. to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compound a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0025] Control group Step 1: In the dark or under yellow light conditions, add 70-90 parts of polyacrylic resin, 70-90 parts of organic solvent, 2-8 parts of curing agent, 0.1-4 parts of antistatic agent, 0.2-5 parts of photoinitiator, and 0.5-5 parts of terephthalic acid by weight and mix. After adding each component, stir and mix at 200-500rpm for 5-10 minutes until uniform to form a viscosity-reducing adhesive solution.

[0026] Step 2: evenly apply the viscosity-reducing adhesive liquid on the surface of the substrate layer, and dry it at 80-130° C. to form a viscosity-reducing adhesive layer with a thickness of 3-20 μm.

[0027] Step 3: Compound a release film with a thickness of 20-80μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0028]

[0029] Combined with Table 1, we can see that in terms of toughness, the experimental group B2 has a relatively high elongation at break due to the higher content of polyacrylic resin, curing agent and other ingredients and more sufficient stirring, showing better toughness and being able to withstand greater deformation without breaking during tensile deformation. The experimental group B1 is second, and the control group 1 is relatively weak. In terms of impact resistance, the experimental group B2 also performs well, can absorb more impact energy, and more effectively protect the adhered objects from impact damage, thanks to its optimized formula and preparation process. The experimental group B1 also has a certain improvement in impact resistance, while the control group 1 is relatively poor. In the tensile test, the tensile strength of the experimental group B2 is the highest, indicating that it can better maintain structural integrity when subjected to tension and is not easily broken. The experimental group B1 is better than the control group 1. The tensile strength of the control group 1 is relatively low, and the adhesive failure may occur when subjected to a large tensile force. Thus, it is explained that the present invention strengthens the substrate composed of polyvinyl chloride, propylene oxide and polyethylene terephthalate, and adds nitrile rubber and nano-calcium carbonate for toughening. Polyvinyl chloride has good chemical corrosion resistance and compatibility, polyethylene terephthalate has high strength and good optical properties, nitrile rubber effectively improves toughness and imparts oil and chemical resistance, and nano-calcium carbonate further enhances toughness, so that the substrate can withstand large tension, pressure and external force impact, is not easy to break or damage, and ensures the stability and reliability of the viscosity-reducing film in a variety of complex environments and use conditions. Embodiment 2

[0030] Experimental Group 3 Step A1: dissolving 10% by weight of 4-methylbenzophenone in 40% by weight of benzene, adding 5% by weight of a 48% concentration hydrobromic acid solution, and heating the mixture to 60° C. under light to obtain an initial reactant; Step A2: 3% by weight of 27.5% concentration hydrogen peroxide is added dropwise to the initial reactant. After the addition is completed, the mixture is kept warm, then cooled to 20-30° C., 2% by weight of bromine is added, and after mixing, the organic phase is washed with a sodium carbonate solution until it becomes weakly alkaline to obtain an organic phase; Step A3: adding 3% by mass of triethanolamine to the organic phase, heating and reflux, so that the quaternary ammonium salt is precipitated in the solvent benzene in the form of a solid, and cooling to 60° C. to obtain a pre-reactant; Step A4: 5% by mass of n-butyl isocyanate was added dropwise to the pre-reactant to carry out temperature-controlled reaction. After the reaction was completed, the temperature was lowered to 26° C., the product was separated by filtration, and the modified photoinitiator was obtained after drying.

[0031] Experimental Group 4 Step A1: dissolving 10% by weight of 4-methylbenzophenone in 40% by weight of benzene, adding 5% by weight of a 48% concentration hydrobromic acid solution, and heating the mixture to 60° C. under light to obtain an initial reactant; Step A2: 3% by weight of 27.5% concentration hydrogen peroxide is added dropwise to the initial reactant. After the addition is completed, the mixture is kept warm, then cooled to 20-30° C., 2% by weight of bromine is added, and after mixing, the organic phase is washed with a sodium carbonate solution until it becomes weakly alkaline to obtain an organic phase; Step A3: adding 3% by mass of triethanolamine to the organic phase, heating and reflux, so that the quaternary ammonium salt is precipitated in the solvent benzene in the form of a solid, and cooling to 60° C. to obtain a pre-reactant; Step A4: 5% by mass of n-butyl isocyanate was added dropwise to the pre-reactant to carry out temperature-controlled reaction. After the reaction was completed, the temperature was lowered to 26° C., the product was separated by filtration, and the modified photoinitiator was obtained after drying.

[0032] Experimental group b3 Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator prepared in experimental group 3, and terephthalic acid are added to the reaction kettle in order according to 70:70:2:0.1:0.2:0.5. After each component is added, it is stirred and mixed at 200 rpm for 5 minutes. After the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer, and drying the coating at 80° C. to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compound a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0033] Experimental group b4 Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator prepared in experimental group 4, and terephthalic acid are added to the reaction kettle in the order of 90:90:8:4:5:5. After each component is added, it is stirred and mixed at 500 rpm for 10 minutes. After the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer, and drying the coating at 130° C. to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compound a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

[0034] As shown in Table 2, combined with Example 1 and Example 2, the double-sided UV anti-viscosity film prepared by the present invention effectively improves toughness and imparts oil and chemical resistance. Nano calcium carbonate further enhances toughness, so that the substrate can withstand greater tension, pressure and external force impact, and is not easy to break or damage, ensuring the stability and reliability of the anti-viscosity film in a variety of complex environments and use conditions, so that the anti-viscosity film has both hardness and elasticity after curing, and can maintain its shape and withstand external forces. The modified photoinitiator is synthesized through a specific complex preparation process, and the components work synergistically to effectively initiate the polymerization of acrylate monomers, so that the glue quickly and evenly changes from liquid to solid, ensuring that the anti-viscosity film has a good curing effect, and is firmly and persistently adhered.

[0035]

[0036] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A double-sided UV anti-viscosity film, characterized in that: The invention comprises the following components by weight: 100-120 parts of reinforcing substrate; 70-90 parts of polyacrylic resin; 70-90 parts of organic solvent; 2-8 parts of curing agent; 0.1-4 parts of antistatic agent; 0.2-5 parts of modified photoinitiator; 0.5-5 parts of terephthalic acid; Wherein, the specific preparation method of the reinforced substrate is as follows: Step S1: drying polyvinyl chloride, propylene oxide and polyethylene terephthalate respectively, and after drying, placing them in a reaction kettle for stirring, and obtaining a primary mixture after stirring; Step S2: adding a rubber toughening agent and a nanomaterial to the premix, and stirring again to obtain a premix; Step S3: adding the premix into a twin-screw extruder for mixing and plasticizing, extruding the prefabricated substrate in the shape of a sheet through a die after mixing, and cooling the premix to 40° C. by air cooling to obtain a reinforced substrate.

2. A double-sided UV anti-viscosity film and a preparation method thereof according to claim 1, characterized in that: In the step S1, the polyvinyl chloride, propylene oxide and polyethylene terephthalate are dried in an oven at 80-100° C. for 2-4 hours, the mass ratio of polyvinyl chloride, propylene oxide and polyethylene terephthalate is 30:30:40, the stirring speed is 500-1000 rpm, and the stirring time is 10-20 minutes.

3. A double-sided UV anti-viscosity film according to claim 1, characterized in that: In the step S2, the rubber toughening agent is a nitrile rubber with an acrylonitrile content of 40%, the nano material is nano calcium carbonate, the amount of the nitrile rubber is 5%-15% of the total mass of polyvinyl chloride, propylene oxide and polyethylene terephthalate, and the amount of the nano calcium carbonate is 1%-5% of the total mass of polyvinyl chloride, propylene oxide and polyethylene terephthalate.

4. A double-sided UV anti-viscosity film according to claim 1, characterized in that: The specific preparation of the modified photoinitiator is as follows: Step A1: dissolving 4-methylbenzophenone in benzene, adding 48% hydrobromic acid solution, and heating to 60° C. under light to obtain an initial reactant; Step A2: adding 27.5% hydrogen peroxide to the initial reactant, keeping the temperature after the addition, then cooling to 20-30°C and adding bromine, washing the organic phase with a sodium carbonate solution to a weak alkaline state after the mixing is completed to obtain an organic phase; Step A3: adding triethanolamine to the organic phase, heating and refluxing to precipitate the quaternary ammonium salt in the solvent benzene in the form of a solid, and cooling to 60° C. to obtain a pre-reactant; Step A4: n-butyl isocyanate is added dropwise to the pre-reactant to carry out temperature-controlled reaction. After the reaction is completed, the temperature is lowered to 26° C., the product is separated by filtration, and the modified photoinitiator is obtained after drying.

5. A double-sided UV anti-viscosity film according to claim 4, characterized in that: The mass fraction of the 4-methylbenzophenone is 10%-30%, the mass fraction of benzene is 40%-60%, the mass fraction of the hydrobromic acid solution is 5%-15%, the mass fraction of hydrogen peroxide is 3%-8%, the mass fraction of bromine is 2%-6%, the mass fraction of triethanolamine is 3%-10%, and the mass fraction of n-butyl isocyanate is 5%-12%.

6. A double-sided UV anti-viscosity film according to claim 4, characterized in that: The illumination in step A1 is LED green light illumination, the heat preservation time in step A2 is 30 minutes, and the heating reflux time in step A3 is 1-8 hours.

7. A method for preparing a double-sided Uv anti-viscosity film, characterized in that: The following steps are involved: Step B1: under the condition of yellow light, polyacrylic acid resin, organic solvent, curing agent, antistatic agent, modified photoinitiator and terephthalic acid are added into the reaction kettle in order, and each component is stirred and mixed after being added, and after the stirring is completed, a viscosity-reducing adhesive solution is obtained; Step B2: coating the viscosity-reducing adhesive liquid on the surface of the reinforcing substrate layer, and drying the coating to obtain a viscosity-reducing adhesive layer with a thickness of 3-20 μm; Step B3: Compounding a release film with a thickness of 20-80 μm on the surface of the anti-viscosity adhesive layer to form a double-sided UV anti-viscosity film.

8. The method for preparing a double-sided UV anti-viscosity film according to claim 7, characterized in that: In step B1, the organic solvent is acetone, the curing agent is ethylenediamine, and the antistatic agent is dodecyltrimethylammonium chloride.

9. The method for preparing a double-sided UV anti-viscosity film according to claim 7, characterized in that: In the step B1, the stirring speed is 200-500 rpm, the stirring time is 5-10 min, and the drying temperature in the step B2 is 80-130° C.